Hotel Purchasing Management and Risk Control: A Case Study of H Hotel - Lin, Yibin; Benjasak, Chonlakan (Science, Technology, and Social Sciences Procedia, 2021)
In recent years, with the rapid growth of China’s economy and national income and the rise of tourism. This not only brings new development opportunities to the hotel industry, but also poses great challenges in the fierce market environment, especially the COVID-19 pandemic in 2020 - 2021. Although the epidemic eased in the second half of 2021, the overall situation is still not optimistic. In such a competitive market environment, the hotel need to control the cost to win the competitive advantage. The purchasing department as the main departments in the hotel operation cost management, and it involves multiple management link which affect the hotel’s operation efficiency and service level. Therefore, the aim of this study is to provide a more comprehensive perspective and understanding of hotel purchasing management by showing the relationship between the hotel’s upstream suppliers and the hotel’s internal operations, as well as the hotel’s overall procurement management system. This study mainly adopts the case study strategy by using qualitative research. Data for this study were collected by using in-depth interview from the hotel managers, as well as analyzing existing hotel policies, rules and procedures. The results show that the procurement management of the hotel industry has cost waste and procurement management loopholes, which need to be improved according to The Times, the market and customer needs. Hotel procurement management has to constantly strengthen the management of suppliers and the construction of internal procurement management system, in order to decrease purchase costs, reduce procurement risks, so as to increase the profits of the hotel. The findings of this paper will provide some suggestions for hotels to improve the efficiency of purchasing management.